Generalized Deferred Statistical Convergence in Credibility Spaces: New Perspectives in the Ideal Setting - Kişi, Ömer; Savaş, Rabia (Prof. Dr. Mehmet Zeki SARIKAYA, 2026)
In this paper, we define the idea of ?-deferred statistical convergence for fuzzy variable sequences in credibility. We also explore the relationships between ?-deferred statistical convergence and strongly ?-deferred Cesàro summability in the credibility of these sequences. Our findings show that in credibility spaces, a sequence is strongly ?-deferred Cesàro summable in credibility if and only if it is ?-deferred statistically convergent in credibility. Additionally, we propose the concept of ?-deferred statistically Cauchy sequences in the context of credibility. © 2026, Prof. Dr. Mehmet Zeki SARIKAYA. All rights reserved.
Keywords: Credibility space; ideal convergence; statistical convergence